De- Westernizing Media Theory to Make Room for African Experience - Nyamnjoh, Francis B. (Popular Media, Democracy and Development in Africa, 2010)
How should one think about popular media in the African context? Should we attempt to understand and analyse the increasing proliferation of tabloids, reality television shows, pop music, websites and mobile communications through the analytical frameworks constructed by scholars in the Global North, or does Africa pose unique research questions? Is there a danger of either essentializing Africa by treating her as ‘different’, or by ignoring her specificity by approaching her media via Western theoretical constructs? The scholar wishing to understand the interface between popular media, development and democracy in contemporary African societies is faced with a complex double bind. Elsewhere (Nyamnjoh 2005: 2-3) I have argued that African worldviews and cultural values are doubly excluded from global media discourses, first by the ideology of hierarchies and boundedness of cultures, and second by cultural industries more interested in profits than the promotion of creative diversity and cultural plurality. Little attention is accorded to how Africans negotiate and navigate the various identity margins and cultural influences in their lives, in ways that are not easily reducible to simple options or straightforward choices. The consequence of rigid dichotomies or stubborn prescriptiveness based on externally induced expectations of social transformation is an idea of democracy hardly informed by popular articulations of personhood and agency in Africa, and media whose professional values and content are not in tune with the expectations of those they purport to serve. The predicament of media practitioners in such a situation, as well as those wishing to understand African media practice through media theory, is obvious: to be of real service to liberal democracy and its expectations of modernity, they must ignore alternative ideas of personhood and agency in the cultural communities within which such practices take place and of which such practitioners and, often, scholars form part. Attending to the interests of particular cultural groups as strategically essential entities risks contradicting the principles of liberal democracy and its emphasis on civic citizenship and the autonomous individual, which media practitioners in African societies are being held accountable to.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

New Queer Cinema 2.0?: Lesbian-focused Films and the Internet. - Beirne, Rebecca (Screen, 2014)
The Internet distribution of lesbian-focused films seen as an example of the ways in which independent producers and distributors are offering their films for sale on the web. Incl. a table comparing costs and number of films available across a range of legal and illegal sites.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Queer Film Ecosystem: Symbolic Economy, Festivals, and Queer Cinema's Legs. - Damiens, Antoine (Studies in European Cinema, 2018)
Stresses the crucial importance of LGBT festivals in promoting examples of queer cinema throughout Europe and the USA.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Narrating Our History: Selections from a Dialogue among Queer Media Artists from the African Diaspora - Ferrera-Balanquet, Raúl; Harris, Thomas Allen; Frilot, Shari; Gilliam, Leah; Suggs, Dawn; Taylor, Jocelyn; Welbon, Yvonne; Juhasz, Alexandra (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The first time I spoke in public about my work was during the Los Angeles Lesbian and Gay Festival in 1990. Cheryl Dunye was the only other woman of color on the panel. When I asked a question regarding funding, I naïvely stated that funding was not a prob lem for me considering the fact that my work at that time was of medium to low production quality. I had minimal access to a low-end production facility, and my piece was only five minutes long. I was alluding to the fact that it has been “easy” for me.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Creating the World Anew: Black Lesbian Legacies and Queer Film Futures - Gumbs, Alexis Pauline (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Deeply grounded in the legacy of Black lesbian artists, writers, and filmmakers, current Black lesbian filmmakers are helping to build infrastructure for a transformed future using deeply interconnected methods to transform the whole world and (while we’re at it) the meaning of life. This chapter looks at two projects, the established and evolving Queer Women of Color Media Arts Project based in San Francisco and the emerging Queer Renaissance and Black Feminist Film School Project based in Durham, North Carolina, as examples of the robust future of Black lesbian filmmaking as a transformative community-building practice. The Queer Women of Color
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

The Book of Ruins and Desire: Interactive Mechatronic Sculpture - Jennings, Pamela L. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The interactive book is a term heard frequently in reference to early experiments in multimedia production. But how to translate the concept of the book into a medium that has no paper, no pages, remains a challenge. Is not a book an object one holds in one’s hands—the cover affected over time by the acids and oils perspiring from the user’s skin, pages turned down and yellowed, torn or marked up? Research could show that the notion of the traditional book has been challenged throughout history. But this challenge has been accelerated with the growing accessibility of new computer
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Ruins and Desire: Interview with Pamela L. Jennings - WELBON, Yvonne (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In the 1990s I lived in New York City. I moved to New York City shortly after graduating from Oberlin College, in Ohio. I lived there for almost a de cade, and during that time I was very actively engaged in continuing my pursuit of a career in photography. Photography was my first form of visual art going back to junior high school. I enrolled in the New York University International Center for Photography master’s program because I really wanted to understand what it was to be a photographer. At that time I was very interested in street photography.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

DV-made Tibet: Domestic Videos, Elite Films, and the Work of Pema Tseden - Barnett, Robert (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
In the three decades after 1980, major changes took place in the ways in which culture in Tibet was produced, transmitted, and consumed.¹ These changes, however, were not evidence of the radical transformation often claimed as the result of digitization, but were brought about by earlier forms of technological development. In terms of music and radio, it was the arrival of cheap cassette players and recorders in Tibet in the late 1980s that allowed Tibetans to choose for the first time when to listen and, within the limits allowed by the market and the government, what to listen to (Dhondup
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Filming Power and the Powerless: Zhao Liang’s Crime and Punishment (2007) and Petition (2009) - Li, Jie (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
This article discusses two recent works by emerging documentary auteur Zhao Liang, Crime and Punishment(2007) and Petition(2009). These penetrating observations of state-society relations in contemporary China render visible those who are un(der)represented, critique the deception of mass media images, and show the various complex ways in which power is connected to surveillance and visibility. Thus the filmmaker, his camera, and the spectators are implicated in power relationships as we cast voyeuristic, panoptic, activist, empathetic, or critical gazes upon the representatives of state power and upon the disenfranchised.
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Spectacular Crowd: Representing the Masses in DV Documentary - Shen, Shuang (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
In their introduction to a collaborative study of crowds organized by the Stanford Humanities Lab in 2000, Jeffrey T. Schnapp and Matthew Tiews observe that while the first half of the twentieth century witnessed a rise of collective social action and various forms of mass assembly, the second half was a period of the decline of collective political formations and the replacement by virtual and media-based assemblies for physical crowds (Schnapp and Tiews 2006, xi). The postindustrial political economy in the West is “characterized by the coexistence of media aggregation and bodily disaggregation,” Schnapp and Tiews claim (xi).
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); _Nettoyé

The Cruelty of the Social: Xianchang, Intersubjectivity, and Interobjectivity - Sniadecki, J. P. (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
At the closing awards ceremony for the 7th Annual DOChina Festival held in May 2010 in Songzhuang—a gentrified artists’ village at the far eastern edge of the Beijing municipality—young animator, poet, and filmmaker Xue Jianqiang was recognized with an honorable mention for his haunting documentary Martian Syndrome. The award came with 2000 RMB, a Panasonic DV camera (the jury’s official comments noted that Xue lacked his own camcorder and had to borrow one to make his film), and the chance to speak before a gathering of who’s who in Chinese independent documentary filmmaking.
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); 5-Identités diasporiques; _Nettoyé

DV and the Animateur Cinema in China - Voci, Paola (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Film scholarship on the movie-making, movie-viewing, and movie-circulating practices that have developed since the mid-1990s in China has appropriately emphasized the role played by the rise of digital video (DV) and its impact on independent and, in particular, documentary filmmaking. In this chapter, I want to explore one line of development in DV independent production that has received much less attention—what I call animateur cinema—which concerns short digital animations that are made by and/or circulated for online (or on-mobile) moviemakers/viewers. Fan-originated digital animation or egao animation can also be found online, but my focus is on animateur cinema
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Recalcitrance of Reality: Performances, Subjects, and Filmmakers in 24 City and Tape - Wang, Qi (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Since its beginning in the early 1990s, independent Chinese documentary has steadily built a reputation with its unflinching presentation of the underbelly of China’s economic boom and social sea changes. Individuals and groups whose experiences register the drastic costs of this process have become the most natural and common subject matter of independent documentaries. From the struggling artists who were among the first to quit state employment and go independent in Bumming in Beijing (Wu Wenguang 1990) to the art-aspiring young migrants from the rural area in The Other Bank (Jiang Yue 1995), from the homeless youngsters in Along the
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Identités diasporiques; _Nettoyé

Toward a Digital Political Mimesis: Aesthetic of Affect and Activist Video - Zhen, Zhang (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
In 1990s post-Reform China, a growing number of people armed with video cameras poured out upon the Chinese landscape to both observe and contribute to the social changes then underway. This digital turn has given us a 'DV China' that includes film and media communities across different social strata and disenfranchised groups. This study takes stock of these phenomena by surveying the social and cultural landscape of grassroots and alternative cinema practices
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); _Nettoyé

Rephrasing the Feitiço: A New Episteme for Perverse Characters - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
Interesting and challenging Hollywood-style films that centre on sexually transgressive characters are not easy to script. Many writers fail as a result of an over-valuation of image at the expense of psychologically complex and challenging subjectivity. A hook for exploring the nature of this phenomenon lies in the notion of ‘involving and disturbing’, with a focus on how films might represent it and how audiences might perceive it, and with attention paid to how characters might be constructed. The chapter expands on how this notion of audience engagement might engage with screenwriting as a design function, aimed to construct characters in visual terms yet through words rather than pictures. In addressing certain epistemic limitations to writing character complexity, an alternative epistemic framing for ‘perverse’ characters is considered in terms of characterological ‘is-ness’, philosophical constitution and behaviours and actions.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Feiticeiro/a as a Materially Identifiable Character: Subjectively Conceived Filmic Participants - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
If the Feiticeiro/a character is to be seen as a structure rather than a substance, the nature of such a structure requires elaboration. If this paradigm is to be internally coherent, a relation of intertwined co-existence between characters and audiences should be built into the framing in ways that provide functional epistemic signposts for mechanisms to translate characters’ intrinsic complexity to these audiences. This chapter approaches this by accounting both for the particularly visual nature of the filmic medium and for how screenplays are not a visual medium themselves and are put to different uses than other forms of narrative writing, therefore requiring distinctive attributes. An orientational notion of relationship between medium and audience is suggested as a foundation for the structure of Feiticeiro/a characters in terms of the philosophical distinction between ‘being’ and ‘appearance’, on the basis of which decisions might be made as to which elements of the character’s constitution should be made apparent and which should either remain invisible or intentionally be obfuscated.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Internally Coherent Feiticeiro/a: A Structure not a Substance - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
The categories for ‘perversion’ in the World Health Organization’s ICD fail to describe people and their practices, thereby obscuring the remarkable singularity of individuals and diversity of groups. Instead, they prescribe heteronormative sexual behaviour, which is unhelpful as a foundation for the Feiticeiro/a character. This chapter explores an alternative epistemic construct, as becomes available in the notion of a focalising character, which reflects a ‘semic’ construct that negates the notion of a ‘pervert’ character as a substance, but instead embraces the notion of a Feiticeiro/a character as a structure. The chapter further explores the philosophical nature of this structure as it relates to the thematic elements of a narrative whilst engaging in believable activities in a material world. The chapter then suggests an approach to structure based in a phenomenological notion of the replacement of ‘substance’ with ‘form’/‘structure’ as the foundation of meaning.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Towards an Episteme for the Feiticeiro/a: Realism in Character Construction - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
An episteme for the Feiticeiro/a as a filmic character who is ‘perverse’ needs a form if it is to be useful to writers wanting to construct complex transgressive sexual characters. The beginnings of this framing are productively associated with the semiotic notion of ‘connotation’. This chapter explores what is meant by complexity in character construction and suggests a framing focused on character as an embodied being as a helpful starting-point for an episteme for characterological ‘perversion’. The chapter explores this as a non-foundationalist framing that transcends problematic Cartesian distinctions, concrete object materiality and woolly broad-stroke statements of a disembodied discursive constitution of social and personal experience.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Writing ‘Perverse’ Behaviour for the Feiticeiro/a: Revisioning the ICD Diagnostic Criteria - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
If the Feiticeiro/a as a psychologically defined and complex character is to be seen as an embodied form/structure (not substance) that exists in dialectical relationships between self, other and discursive constructions of society, a clearer indication should be made about what kinds of behaviours or actions he/she should engage in. This chapter explores how psychiatric diagnostic criteria fail to provide assistance, despite professing to authoritatively mark stable, reliable and accurate epistemic boundaries to sexual activity. The chapter thereby addresses questions of the description of actions versus the demarcation of thoughts, objects, feelings and time as invisible and abstracted notions that are virtually the opposite of what is useful for an episteme for the Feiticeiro/a. It also approaches how the diagnostic criteria codify ‘perverse’ activity in determinist terms, thereby insidiously refusing an epistemic construct of action into which is built an acknowledgement of the behaviours of the Feiticeiro/a as a complex subjectivity.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

African American Cinema Through Black Lives Consciousness - Reid, Mark A. (Wayne State University Press, 2019)
"African American Cinema through Black Lives Consciousness uses critical race theory to discuss American films that embrace contemporary issues of race, sexuality, class, and gender. Its linear history chronicles black-oriented narrative film from post-World War II through the presidential administration of Barack Obama. Editor Mark A. Reid has assembled a stellar list of contributors who approach their film analyses as an intersectional practice that combines queer theory, feminism/womanism, and class analytical strategies alongside conventional film history and theory. Taken together, the essays invigorate a "Black Lives Consciousness," which speaks to the value of black bodies that might be traumatized and those bodies that are coming into being-ness through intersectional theoretical analysis and everyday activism. The volume includes essays such as Gerald R. Butters's, "Blaxploitation Film," which charts the genre and its uses of violence, sex, and misogyny to provoke a realization of other philosophical and sociopolitical themes that concern intersectional praxis. Dan Flory's "African-American Film Noir" explains the intertextual-fictional and socio-ecological-dynamics of black action films. Melba J. Boyd's essay, "'Who's that Nigga on that Nag?': Django Unchained and the Return of the Blaxploitation Hero," argues that the film provides cultural and historical insight, "signifies" on blackface stereotypes, and chastises Hollywood cinema's misrepresentation of slavery. African American Cinema through Black Lives Consciousness embraces varied social experiences within a cinematic Black Lives Consciousness intersectionality. The interdisciplinary quality of the anthology makes it approachable to students and scholars of fields ranging from film to culture to African American studies alike."
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Introduction: What Is Queer Production Studies/Why Is Queer Production Studies? - Martin Jr., Alfred L. (Journal of Film and Video, 2018)
An introduction is presented in which the editor discusses various reports within the issue on topics including where and how queerness is produced, the use of paratexts to expand and stop queer readings of films, and queers' non-reliance on mainstream media to produce queer stories.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); _Nettoyé

Queer Representations in Chinese-language Film and the Cultural Landscape - Chao, Shi-Yan (Asian visual cultures, 2020)
This book provides a cultural history of queer representations in Chinese-language film and media, negotiated by locally produced knowledge, local cultural agency, and lived histories. Incorporating a wide range of materials in both English and Chinese, this interdisciplinary project investigates the processes through which Chinese tongzhi/queer imaginaries are articulated, focusing on four main themes: the Chinese familial system, Chinese opera, camp aesthetic, and documentary impulse. Chao's discursive analysis is rooted in and advances genealogical inquiries: a non-essentialist intervention into the "Chinese" idea of filial piety, a transcultural perspective on the contested genre of film melodrama, a historical investigation of the local articulations of mass camp and gay camp, and a transnational inquiry into the different formats of documentary. This book is a must for anyone exploring the cultural history of Chinese tongzhi/queer through the lens of transcultural media.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Muséologie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); _Nettoyé

Queer/Palestinian Cinema: A Critical Conversation on Palestinian Queer and Women's Filmmaking - Jankovic, Colleen; Nadia, Awad (Camera Obscura: Feminism, Culture, and Media Studies, 2012)
While expanding critiques of pinkwashing have drawn increasing attention to how queer issues in Israel and the Occupied Palestinian Territories are perniciously mobilized by a network of lobby groups, Brand Israel initiatives, and international gay and lesbian organizations, these critiques often fail to consider how queer Palestinians mobilize and understand themselves. This article reports on an October 2011 panel and film screening at Yale University and the Hagop Kevorkian Center for Near Eastern Studies at New York University. “Queer/Palestinian: Critical Strategies in Palestinian Queer and Women's Filmmaking” uniquely focused on questions of queerness and Palestine through a program of eight new Palestinian visual productions. The program brought together Palestinian film scholars, filmmakers, visual artists, and curators for a discussion of queer and feminist artistic practice in relation to Palestinian strategies for resistance. Together, the “Queer/Palestinian” films suggest the urgency for Palestinian visual artists to persistently generate new means of expressing, embodying, and critiquing visions for Palestinian society. Films such as Victoria Moufawad-Paul's Nus Enssas/ صيصنصن (Canada, 2011) and Raafat Hattab's Hourieh (Palestine, 2011) explore issues ranging from queer diasporic solidarity politics and challenges to out/closeted binaries and to the creative reinscription of nakba narratives. Nadia Awad's Two Adaptations of the Same Novel (US, 2011), Suzy Salamy's 1982/2006 (US, 2006), and Moufawad-Paul's Rejoice, O My Heart / يبلق اي حرفا (Canada, 2011) suggest an irreverent queer strategy by undermining the narrative conventions and visual codes of mainstream news media and popular US and Egyptian cinema. Salamy's video, previously projected through mobile exhibition on city buildings, and Eli Rezik's online “web-movies” Living Alone without Me (Palestine, 2011) and Between Us Two (Palestine, 2011) compelled a panel discussion of alternative means of distribution and exhibition. Finally, Alaa AbuAsad's Masturbate bil beit (Palestine, 2011) rounded out the program with an explicitly erotic and unapologetically political version of the meeting of “queer” and “Palestinian.”
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Europe (corpus analysé); 5-Identités diasporiques; _Nettoyé